2019
DOI: 10.1159/000505204
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Approach to Gastric Acid Suppression: Past, Present, and Future

Abstract: Less than 2 centuries have elapsed since the identification of hydrochloric acid in the stomach. The clarification of the molecular mechanisms allowed the effective therapeutic suppression of gastric acid secretion. The spectacular advances in the treatment of acid-related disorders represent a synthesis of the contributions of several brilliant pharmacologists, basic scientists, and clinical physicians. Effective gastric acid suppressive therapy has dramatically improved the therapy and outcome of acid-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…It was known that the differences in acid inhibition lead to different eradication rate and strong acid inhibition increases the efficacy of H. pylori . 42 44 Rabeprazole and esomeprazole could provide better control of gastric acid, leading an increase in pH value to the neutral range within a short time than older PPIs when they administered at the standard doses; thus, strengthened the effects of antibiotics. 45 47 In addition, 24-h intragastric pH monitoring had shown that 10 and 20 mg of rabeprazole twice daily have a comparable antisecretory effect on the median pH value and percent time of >4.0, >5.0, >6.0, and >7.0 for 24 h. 21 This might explain why the eradication rate in the high-dose group was not better than that in the standard-dose group.…”
Section: Discussionmentioning
confidence: 99%
“…It was known that the differences in acid inhibition lead to different eradication rate and strong acid inhibition increases the efficacy of H. pylori . 42 44 Rabeprazole and esomeprazole could provide better control of gastric acid, leading an increase in pH value to the neutral range within a short time than older PPIs when they administered at the standard doses; thus, strengthened the effects of antibiotics. 45 47 In addition, 24-h intragastric pH monitoring had shown that 10 and 20 mg of rabeprazole twice daily have a comparable antisecretory effect on the median pH value and percent time of >4.0, >5.0, >6.0, and >7.0 for 24 h. 21 This might explain why the eradication rate in the high-dose group was not better than that in the standard-dose group.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the Histamin H2-receptor antagonists, PPIs represent the gold-standard therapy in the gastric acidrelated disorders [51]. Omeprazole (a weakly basic compound, pKa ~4) is a gastric anti-secretory agent.…”
Section: Gi Ph and Drug Many Weakly Basic Drugs Exhibitmentioning
confidence: 99%
“…Similarly, the compound 4f and 4m produced a relatively moderate effect in reducing the intestinal fluid accumulation with a mean value of 125 ± 5 and 160.3 ± 1.6, respectively (Figure 4). These results of antisecretory effects indicate that 2‐mercapto‐benzimidazole derivatives reduce gastric secretions and can be a potential drug candidate for treating gastric ulcers (Herszényi, Bakucz, Barabás, & Tulassay, 2020).…”
Section: Resultsmentioning
confidence: 94%